2023
DOI: 10.3390/en16041673
|View full text |Cite
|
Sign up to set email alerts
|

Performance Simulation of Solar Trough Concentrators: Optical and Thermal Comparisons

Abstract: The solar trough concentrator is used to increase the solar radiation intensity on absorbers for water heating, desalination, or power generation purposes. In this study, optical performances of four solar trough concentrators, viz. the parabolic trough concentrator (PTC), the compound parabolic concentrator (CPC), the surface uniform concentrator (SUC), and the trapezoid trough concentrator (TTC), are simulated using the Monte Carlo Ray Tracing method. Mathematical models for the solar trough concentrators ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…SolidWorks solar water heater CAD model utilizing empirical principles allows visualization and representation of suggested design modifications. The positivist approach uses recognized data sources and empirical methodologies to conduct a thorough and systematic study on solar water heater efficiency enhancement [47].…”
Section: Methodsmentioning
confidence: 99%
“…SolidWorks solar water heater CAD model utilizing empirical principles allows visualization and representation of suggested design modifications. The positivist approach uses recognized data sources and empirical methodologies to conduct a thorough and systematic study on solar water heater efficiency enhancement [47].…”
Section: Methodsmentioning
confidence: 99%
“…First, solar-concentrated photoreactors may provide excessively high light irradiance and reaction temperatures for photocatalytic reactions [17,102]. Figure 7a shows the ability of some typical PTRs [45,62,[103][104][105], PDRs [49,[106][107][108], SPTs [69] and LFRs [70,72,109] to concentrate solar energy. Usually, these solar concentrators are used to concentrate solar energy efficiently to produce high temperatures which can be employed in thermal engineering processes such as in photo-thermal power plants.…”
Section: Problems In Solar-concentrated Photoreactorsmentioning
confidence: 99%
“…Moreover, there is a knowledge gap between solar optical analyses and the thermal and deformation performances of STCs. To provide guidance for scholars, enterprises, and engineers in choosing the STC type for various application fields, the widely used STC types, such as parabolic trough concentrators (PTCs), compound parabolic concentrators (CPCs), surface uniform concentrators (SUCs), and trapezoid trough concentrators (TTCs), were compared by Cao et al [4]. Through a detailed numerical simulation, they concluded that SUCs hold the smallest equivalent stress, which is favorable for the long-term operation of solar thermal utilization systems.…”
Section: Renewable Energy Technologiesmentioning
confidence: 99%